Exercise and Cognitive Training Intervention Improves Self-Care, Quality of Life and Functional Capacity in Persons With Heart Failure. (February 2022) - Gary, Rebecca A.; Paul, Sudeshna; Corwin, Elizabeth; Butts, Brittany; Miller, Andrew H.; Hepburn, Kenneth; Waldrop, Drenna
This study evaluated a 12-week, home-based combined aerobic exercise (walking) and computerized cognitive training (EX/CCT) program on heart failure (HF) self-care behaviors (Self-care of HF Index [SCHFI]), disease specific quality of life (Kansas City Cardiomyopathy Questionnaire [KCCQ]), and functional capacity (6-minute walk distance) compared to exercise only (EX) or a usual care attention control (AC) stretching and flexibility program. Participants ( N = 69) were older, predominately female (54%) and African American (55%). There was significant improvement in self-care management, F (2, 13) = 5.7, p < .016; KCCQ physical limitation subscale, F (2, 52) = 3.4, p < .039; and functional capacity (336 ± 18 vs 388 ± 20 m, p < .05) among the EX/CCT participants. The underlying mechanisms that EX and CCT targets and the optimal dose that leads to improved outcomes are needed to design effective interventions for this rapidly growing population.